The moving-slab Heating in the furnace for various production plans - Istadi Istadi; Y. Bindar; Koswara Koswara (Reaktor, 2002)
The reheating furnace in occasional production time has to be charged with slabs having fifferent sizes in length, ridth and thickness. This production plan was put due to economical and productivity consideration. Moreover in the future development, the slab grade might be improved to hight grades. It is our expectation that the furnace can be fire for different production plans above. The strategy for firing the burners from zone to zone has to  be determined precisely to meet the designed heating curves for the various slab. A suggest to guide in the formulations of the furnace firing strategy was developed in this work. This suggestion is based on three-dimentional mathematical model for heated slab in the furnace. This mathematical model was coded  for the computational simulation. The  code was able to simulate  furnacthree-dimentional effect of fuenace operational parameters and variety of slab length group. The result reasonably represent the slab-heating curve for different operational parameters. Unsymmetrical firing practices can be shown their effect to the 3D temperature distribution of the slab. Keywords : 3Dtemperature distribution, reheating furnace, slab heating, slab length group